DNA fingerprinting of promising cocoa (Theobroma cacao L.) varities of kau - Sujith S S (Centre for plant biotechnology and molecular biology, College of Horticulture, 2016)
Cocoa (Theobroma cacao L.) also known as ‘chocolate tree’ is a major cash crop of tropical countries and belongs to the family Malvaceae. The plant is a native of Andes, South America and was introduced to India during 1970s. In India, cocoa is cultivated as an important intercrop with in coconut, arecanut, rubber, oil palm etc. The statistics shows that, 80 per cent of cocoa plantations in India is established with planting materials distributed from Kerala Agricultural University (KAU). In India, the genetic base of cocoa is widened by the systematic introduction of germplasm from University of Reading, UK. Cocoa Research Centre (CRC), KAU holds Asia’s largest germplasm with 640 accessions. Exploitation of these germplasm has resulted in the release of 15 cocoa varieties from KAU. Central sub-committee on crop standards, notification and release of varieties for agricultural crops has made it mandatory to provide DNA finger printing data along with the varieties where ever the proposal for national release/ notification is submitted. DNA markers, that are not subjected to environmental influences act as an efficient tool to identify and differentiate accessions and cultivars which are similar in morphological characteristics and with indistinct traits. DNA finger printing is successfully applied for cultivar identification, controlling seed purity of hybrids and checking the genetic similarity between cultivars. Hence, the technique act as a powerful tool to protect Plant Breeder’s Right (PBR). In the present investigation, eight promising cocoa varieties CCRP 1, CCRP 2, CCRP 4, CCRP 5, CCRP 6, CCRP 7 (selections), and CCRP 8 and CCRP 9 (hybrids) released from KAU were characterized using morphological and molecular markers. For morphological characterization, six qualitative and nine quantitative characters were recorded. And it was observed that, CCRP 6 and CCRP 8 were superior based on the performance of their yield contributing characters. Molecular characterization was performed with genomic DNA isolated using modified Chandrakant’s (2014) protocol. Based on the polymorphism, ten ISSR (inter simple sequence repeats) and eleven SSR (simple sequence repeats) primers were selected. These selected primers were used for developing DNA fingerprints of varieties under study. In the further analysis, amplicon generation pattern were carefully scored to locate polymorphism. IndividualISSR and SSR amplification pattern further converted into variety wise fingerprints and thus consolidated DNA fingerprints on each marker system were developed. ISSR primers UBC 810 and UBC 826 were found to differentiate CCRP 6 from other genotypes. Primers UBC 827, UBC 846 and UBC 866 were generated unique amplicons in CCRP 9. UBC 841 and UBC 846 were capable of distinguishing CCRP 5 from other genotypes. Primers UBC 835 and UBC 866 were generated amplicons in hybrids CCRP 8 and CCRP 9 alone and the markers can be used for differentiating these hybrids. SSR marker analysis was performed using selected eleven primers. Selected primers generated polymorphic amplicons and were capable of distinguishing between varieties. Primer mTcCIR 8 generated unique amplicon at 220 and 420 base pairs (bp) in CCRP 1 and CCRP 4 respectively which was a fingerprint for those varieties. The unique amplicon generated by mTcCIR 33 at 320 bp was a fingerprint of CCRP 2. Polymorphic amplicons generated by mTcCIR 42 at 200 bp (CCRP 4) and at 220 bp (CCRP 9) were fingerprints of respective varieties. In future, more morphological characters have to be screened and correlated with the markers shared by two or three varieties. This will help to know whether the shared bands are responsible for expression of some distinct traits. DNA fingerprints for remaining seven released cocoa varieties also have to be designed.